A self-supporting photonic crystal fiber based on microfluidics, a preparation method and applications thereof
Patent Information
- Application Number
- CN202611366518.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-27
AI Technical Summary
然而,这种纯物理堆积模式存在一个根深蒂固的物理缺陷:粒子间仅依靠范德华力、静电力或毛细管力等弱相互作用维持稳定,缺乏强化学键连接,导致材料表现出典型的“脆性陶瓷态”特征
(1)本发明通过微流控受限空间诱导胶体粒子有序组装,并利用原位光交联技术在粒子间构建共价键网络,实现从“脆性陶瓷态”到“柔性橡胶态”的转变,有效抵抗毛细管收缩应力;同时利用交联网络锁定粒子位置,纤维在溶剂挥发后能保持完美的三维有序结构,呈现出鲜艳的结构色,并通过交联网络赋予纤维良好的溶胀-收缩弹性,使其具有溶剂响应的结构色可逆变化特性,当纤维溶胀时,晶格常数增大,反射波长红移;当纤维收缩时,晶格常数减小,反射波长蓝移;
Smart Images

Figure CN122980053A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photonic crystal materials technology, specifically relating to a microfluidic-based self-supporting photonic crystal fiber, its preparation method, and its application. Background Technology
[0002] Currently, colloidal photonic crystals (CPCs) serve as ideal carriers for achieving structural color and optical manipulation. They primarily rely on the "bottom-up" self-assembly principle of colloidal particles, utilizing entropy and hard-sphere repulsion to induce monodisperse microspheres to form face-centered cubic or hexagonal close-packed structures. However, this purely physical packing mode suffers from a deep-seated physical defect: particles maintain stability solely through weak interactions such as van der Waals forces, electrostatic forces, or capillary forces, lacking strong chemical bonds, resulting in materials exhibiting typical "brittle ceramic" characteristics. This structural weakness is particularly critical in the microfluidic fiber preparation process. On one hand, the wet gel fibers at the outlet are highly susceptible to breakage due to a lack of internal support, making continuous collection difficult. On the other hand, during the later solvent evaporation stage, the enormous capillary forces generated at the liquid-gas interface directly cause particle layer slippage or structural collapse, shattering the fibers into powder with an elongation at break typically less than 5%.
[0003] While existing technologies attempt to enhance mechanical properties by introducing polymer matrix infiltration or sol-gel coating, this often comes at the expense of optical performance. Polymer filling of particle gaps disrupts the periodic dielectric environment, leading to a weakening or even disappearance of the photonic bandgap, and consequently, a dulling of the structural color. Existing technologies have consistently failed to resolve the contradiction between "long-range ordered assembly of colloidal particles" and "strong covalent bonding between particles"—that is, how to ensure a high degree of order in particle arrangement within microfluidic channels while simultaneously introducing chemical cross-linking at the particle contact interface to resist capillary contraction stress. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a microfluidic-based self-supporting photonic crystal fiber, its preparation method, and its application. This method enables simultaneous ordered assembly and in-situ photochemical locking within a confined space, resulting in a photonic crystal fiber that combines high toughness, high orderliness, and self-supporting properties.
[0005] In a first aspect, the present invention provides a method for fabricating a self-supporting photonic crystal fiber based on microfluidics, characterized by comprising the following steps: Preparing precursor solutions of monodisperse colloidal particles modified with polymerizable functional groups; The precursor solution is injected into the channel of the microfluidic chip to form wet gel fibers in a flowing state; by utilizing the confined space and shear force of the microchannel, the colloidal particles are induced to undergo ordered self-assembly, forming continuous wet gel fibers in the channel. In-situ ultraviolet irradiation treatment was performed on wet gel fibers in a flowing state to obtain gel fibers with cross-linked networks; The gel fibers with cross-linked networks are desolventized to obtain self-supporting photonic crystal fibers. As the solvent evaporates, the interparticle spacing of the colloidal particles decreases and they are tightly packed together, eventually forming self-supporting photonic crystal fibers with regular fiber morphology. The preparation method of the polymerizable functional group modified monodisperse colloidal particle precursor liquid includes: An activated solution is obtained by activating a monodisperse colloidal particle aqueous dispersion with a functional group activator. The activated liquid was modified with functional monomers to obtain a modified liquid; The modified solution was centrifuged, the precipitate was redispersed in water, and a photoinitiator and crosslinking agent were added to obtain a precursor solution of monodisperse colloidal particles modified with polymerizable functional groups. Polymerizable double-bonded functional groups were introduced onto the surface of the colloidal particles by covalent grafting the activated monodisperse colloidal particles with functional monomers.
[0006] Furthermore, the monodisperse colloidal particles include at least one of carboxylated silica colloidal particles, carboxylated polystyrene colloidal particles, carboxylated polymethyl methacrylate, and carboxylated tert-butyl acrylate.
[0007] Furthermore, the particle size of the monodisperse colloidal particles is 180nm~350nm, and the polydispersity index is not higher than 0.050 and not 0. The polydispersity index (PDI) is a key parameter characterizing the uniformity of particle size in the building blocks (colloidal particles) of photonic crystals (with a value greater than 0). A smaller PDI value indicates a narrower particle size distribution and better monodispersity. In the self-assembly process of colloidal photonic crystals, particle size uniformity is a crucial factor determining the formation of long-range ordered structures. When the PDI is not higher than 0.050, particles can pack closely together, forming highly ordered face-centered cubic (FCC) or hexagonal close-packed (HCP) structures, resulting in excellent optical properties, manifested as bright, saturated structural colors. Conversely, if the PDI > 0.05, particle size polydispersity increases significantly, and the coexistence of particles of different sizes introduces severe steric hindrance, leading to a surge in lattice distortion and stacking defects, hindering the formation of long-range ordered structures. In this case, the photonic crystal cannot generate a complete photonic bandgap, losing its selective Bragg reflection capability for specific wavelengths of light, ultimately resulting in dim or even absent structural colors.
[0008] Colloidal photonic crystals are ordered microstructured materials assembled from monodisperse colloidal particles. Their periodic dielectric structure generates photonic band gaps, enabling selective Bragg reflection of specific wavelengths of light. When the band gap is located in the visible light band (380~780nm), the material exhibits a vibrant structural color. According to Bragg's law of diffraction, the center wavelength of the photonic band gap is positively correlated with the particle size of the building blocks. Therefore, to obtain a structural color observable to the naked eye, the particle size of the colloidal particles must be strictly controlled within the range of 180~350nm: a particle size <180nm causes the band gap to blue-shift into the ultraviolet region, rendering it unable to display color; a particle size >350nm causes the band gap to red-shift into the infrared region, rendering it outside the visible range.
[0009] Furthermore, the group activator is at least one selected from 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, and carbonyldiimidazole.
[0010] Furthermore, the functional monomer is at least one selected from hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylic acid, and acrylamide.
[0011] Furthermore, in the preparation of the precursor solution of the polymerizable functional group-modified monodisperse colloidal particles, the mass concentration of the aqueous dispersion of the monodisperse colloidal particles needs to be strictly controlled within 5% to 15%. This concentration range provides suitable particle specific surface area and reaction site density while ensuring good dispersion stability of the system. This allows the coupling agent or functional monomer to have sufficient opportunity to undergo uniform and complete chemical modification with the particle surface, while avoiding agglomeration or uneven modification caused by local overconcentration. When the concentration is below 5%, the number density of colloidal particles in the system is too low, and the total specific surface area is insufficient, resulting in too few reaction sites per unit volume that can participate in surface modification. The coupling agent is relatively excessive and prone to self-condensation or hydrolysis side reactions, reducing the surface modification efficiency. In addition, an overly dilute dispersion will increase the difficulty of subsequent concentration (increasing the mass concentration). Above 15%, the interparticle spacing is too small, the viscosity of the suspension increases significantly, and the surface modifier (such as silane coupling agent, polymerizable monomer, etc.) is difficult to diffuse uniformly in the system, easily causing insufficient particle surface modification and uneven degree of substitution. At the same time, the steric hindrance and electrostatic repulsion are weakened, making it easy for particles to form instantaneous contact, inducing local flocculation or hard agglomeration, destroying monodispersity (increased PDI), and ultimately affecting the long-range order and structural color quality of subsequent photopolymerization assembly or photonic crystals.
[0012] Furthermore, in the process of preparing the precursor liquid of the monodisperse colloidal particles modified with polymerizable functional groups, the functional group activator accounts for 0.2% to 0.6% of the total mass of the aqueous dispersion of monodisperse colloidal particles.
[0013] And / or, in the process of preparing the precursor liquid of the polymerizable functional group-modified monodisperse colloidal particles, the functional monomer accounts for 2% to 8% of the total mass of the aqueous dispersion of the monodisperse colloidal particles.
[0014] Furthermore, the photoinitiator includes 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propanone or 2-hydroxy-2-methylphenylpropanone.
[0015] Furthermore, the crosslinking agent includes at least one of N,N'-methylenebisacrylamide, ethylene glycol dimethacrylate, and trimethylolpropane triacrylate.
[0016] Furthermore, based on the total mass of the monodisperse colloidal particle precursor liquid modified with the polymerizable functional groups, the mass concentration of the monodisperse colloidal particles is 30%~50%; the mass concentration of the photoinitiator is 0.5%~1.5%; and the mass concentration of the crosslinking agent is 0.5%~5%.
[0017] Furthermore, the activation temperature during the activation treatment is 40℃~80℃, and the activation time is 2h~5h.
[0018] Furthermore, the reaction temperature during the modification treatment is 40℃~80℃, and the reaction time is 4h~8h.
[0019] Furthermore, the in-situ ultraviolet irradiation wavelength is 250nm~370nm, the irradiation intensity is 10mW / cm²~200mW / cm², and the irradiation time is 5min~20min. During this process, the photoinitiator decomposes to generate free radicals, which initiate polymerization reactions between double bonds on the surface of colloidal particles and with the crosslinking agent, forming a stable covalent crosslinked network at the particle interface. This network acts like "molecular welding," firmly locking the loose colloidal particles together.
[0020] Furthermore, the agent is volatilized by natural air drying or heating and drying, with a volatilization temperature of 20℃~60℃.
[0021] Secondly, the present invention provides a microfluidic-based self-supporting photonic crystal fiber, which is prepared by the above method. The hollow photonic crystal fiber has a tensile strength of 5 MPa to 10 MPa and an elongation at break of 200% to 800%.
[0022] Thirdly, the present invention provides an application of the above-mentioned microfluidic-based self-supporting photonic crystal fiber in the fabrication of flexible wearable light-emitting devices or smart color-changing textiles.
[0023] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention induces the orderly assembly of colloidal particles through microfluidic confined space and uses in-situ photocrosslinking technology to construct a covalent bond network between particles, realizing the transformation from "brittle ceramic state" to "flexible rubber state", effectively resisting capillary shrinkage stress; at the same time, the crosslinking network locks the particle position, and the fiber can maintain a perfect three-dimensional ordered structure after the solvent evaporates, showing a bright structural color. The crosslinking network also gives the fiber good swelling-shrinkage elasticity, making it have the characteristic of reversible change of structural color in response to solvent. When the fiber swells, the lattice constant increases and the reflection wavelength red shifts; when the fiber shrinks, the lattice constant decreases and the reflection wavelength blue shifts. (2) The self-supporting photonic crystal fiber described in this invention has an elongation at break of 200%~800% and a tensile strength of 5MPa~10MPa. It can be bent and knotted at will without breaking, solving the problem of photonic crystal materials being "brittle like ceramics". It does not require rigid substrate support and can be directly woven into cotton, linen, chemical fiber and other fabrics for the preparation of flexible wearable light-emitting devices, smart color-changing textiles or strain sensors. Attached Figure Description
[0024] Figure 1 This is a flowchart of the microfluidic fabrication process for the self-supporting photonic crystal fiber described in this invention. Figure 2 These are macroscopic optical images of the self-supporting photonic crystal fiber prepared in Example 1 of the present invention, wherein a is an optical image of the prepared self-supporting photonic crystal fiber, b is an optical image of the self-supporting photonic crystal fiber in a knotted state, and c is an optical image of the self-supporting photonic crystal fiber bent into a spiral state. Figure 3 SEM images of the photonic crystal fiber prepared in Example 1 of the present invention are shown, wherein a is an SEM image of the prepared self-supporting photonic crystal fiber, b is a cross-sectional SEM image of the self-supporting photonic crystal fiber, and c is a high-resolution SEM image. Figure 4 The stress-strain curve of the photonic crystal fiber prepared in Example 1 of this invention is shown. Figure 5 The diagram shows the reversible change of structure color in the solvent response of the photonic crystal fiber prepared in Example 1 of this invention. In the diagram, a is an optical photograph of the fiber in its initial dry state, b is an optical photograph of the fiber after being wetted with ethanol solution, and c to f are optical photographs of the fiber after being wetted with ethanol solution and dried at room temperature for 20s, 80s, 100s and 120s, respectively. Figure 6 The diagram shows the flexible weave pattern of the self-supporting photonic crystal fiber described in this invention. In the diagram, position a is a macroscopic view without a light source, position b is an enlarged view of the rectangular portion of position a, and position c is an overall view of the flexible weave pattern. Detailed Implementation
[0025] Hereinafter, embodiments of the present invention will be described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0026] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60~120 and 80~110 are listed for a specific parameter, it is also expected that ranges of 60~110 and 80~120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1~3, 1~4, 1~5, 2~3, 2~4, and 2~5. In this application, unless otherwise stated, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0~5" have been listed in this article, and "0-5" is just a shortened representation of these numerical combinations. In addition, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0027] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0028] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0029] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0030] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0031] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0032] Unless otherwise specified, in this application, the terms "first," "second," "third," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.
[0033] In this application, the terms "multiple", "various", etc., refer to two or more kinds.
[0034] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0035] Unless otherwise stated, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application.
[0036] Unless otherwise specified, all reagents used in the description of this invention are commercially available.
[0037] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention will be further described below in conjunction with specific embodiments and accompanying drawings.
[0038] Example 1 A method for fabricating self-supporting photonic crystal fibers based on microfluidics, such as... Figure 1 The steps shown are as follows: Weigh 200g of an aqueous dispersion of carboxylated polystyrene monodisperse colloidal particles with a particle size of 220nm and a polydispersity index of 0.020. The mass concentration of the aqueous dispersion of monodisperse colloidal particles is 10wt%.
[0039] 0.3 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.4 g of N-hydroxysuccinimide were added to the aqueous dispersion of monodisperse colloidal particles. The mixture was then stirred at 300 rpm for 3 hours in a constant temperature water bath at 60 °C to obtain the activated solution.
[0040] 10g of hydroxyethyl methacrylate was added dropwise to the activated dispersion. The mixture was kept in a 60°C water bath at 300 rpm and stirred for 6 hours to allow the hydroxyethyl methacrylate to be grafted onto the surface of the polystyrene colloidal particles, thus obtaining the modified solution.
[0041] The reacted colloidal particle dispersion was centrifuged at 12,000 rpm for 15 minutes, the supernatant was discarded, and the precipitate was redispersed in deionized water and sonicated for 10 minutes to prepare a dispersion with a mass concentration of 40 wt%. Subsequently, the photoinitiator 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propanone (1.0 wt% of the total mass of the dispersion) and the crosslinking agent ethylene glycol dimethacrylate (2.0 wt% of the total mass of the dispersion) were added, and the mixture was sonicated for another 10 minutes in the dark to form the precursor solution.
[0042] The aforementioned precursor solution was loaded into a syringe, which was then attached to a microinjection pump and injected into a hydrophobically treated polymethyl methacrylate (PMMA) microfluidic chip with a circular cross-section and an inner diameter of 800 μm. The injection flow rate was controlled at 50 μL / min to induce the orderly self-assembly of colloidal particles, forming wet gel fibers from within the microchannel.
[0043] A 365nm ultraviolet LED light source was placed above the chip, and the irradiation intensity was set to 50mW / cm² to irradiate the wet fibers in a flowing state in situ for 10 minutes.
[0044] The prepared photonic crystal fibers were collected in a petri dish and dried in a 40°C forced-air drying oven to obtain self-supporting photonic crystal fibers with a blue structural color. The self-supporting photonic crystal fibers are shown below. Figure 2 and Figure 3 As shown; Figure 4 As shown, the obtained fiber has a tensile strength of 5.7 MPa and an elongation at break of 510%. The fiber exhibits solvent-responsive characteristics, such as... Figure 5 As shown, after being immersed in an ethanol solution for wetting, the structural color shifts to red; it recovers after being removed and dried.
[0045] This embodiment also further prepares flexible braided patterns using the self-supporting photonic crystal fibers obtained during preparation, such as... Figure 6 As shown, the self-supporting photonic crystal fiber of this invention possesses both excellent self-support and high flexibility. The fiber can not only be independently molded but also exhibits excellent weavability. Even under stress and deformation, the fiber retains a stable and vibrant structural color, ensuring its performance reliability during long-term use or repeated stretching. Furthermore, this fiber can be directly used as a specialty yarn in conventional textile processes, successfully producing flexible fabrics with exquisite patterns. This not only verifies the feasibility of processing but also provides an effective material solution for developing novel structural color textiles and wearable devices.
[0046] Example 2 A method for fabricating self-supporting photonic crystal fibers based on microfluidics includes the following steps: Weigh 200g of an aqueous dispersion of carboxylated silica monodisperse colloidal particles with a particle size of 180nm, a polydispersity index of 0.010, and a solid content of 15wt%.
[0047] Add 0.15 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.25 g of N-hydroxysuccinimide to the aqueous dispersion of monodisperse colloidal particles, and activate the mixture by stirring at 200 rpm for 2 hours in a constant temperature water bath at 40 °C to obtain the activated solution.
[0048] Add 4g of hydroxypropyl methacrylate dropwise to the activated dispersion. Maintain a water bath at 40°C and a stirring speed of 200rpm, and continue stirring for 4 hours to allow the hydroxypropyl methacrylate to be grafted onto the surface of the silica particles, thus obtaining the modified solution.
[0049] The reacted colloidal particle dispersion was centrifuged at 16,000 rpm for 30 minutes, the supernatant was discarded, and the precipitate was redispersed in deionized water and sonicated for 15 minutes to prepare a dispersion with a mass concentration of 30 wt%. Then, the photoinitiator 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propanone (0.5 wt% of the total mass of the dispersion) and the crosslinking agent trimethylolpropane triacrylate (0.5 wt% of the total mass of the dispersion) were added, and the mixture was sonicated for another 15 minutes in the dark to form the precursor solution.
[0050] The aforementioned precursor solution was loaded into a syringe, which was then attached to a microinjection pump and injected into a hydrophobically treated polydimethylsiloxane microfluidic chip with a circular cross-section and an inner diameter of 300 μm. The injection flow rate was controlled at 10 μL / min to induce the orderly self-assembly of colloidal particles, forming wet gel fibers from within the microchannel.
[0051] A 250nm ultraviolet LED light source was placed above the chip, and the irradiation intensity was set to 10mW / cm² to irradiate the wet fibers in a flowing state in situ for 5 minutes.
[0052] The prepared photonic crystal fibers were collected in a petri dish and air-dried at room temperature of 20°C to obtain self-supporting photonic crystal fibers with blue structural color. The tensile strength of the obtained fibers was 5.0 MPa and the elongation at break was 800%.
[0053] Example 3 A method for fabricating self-supporting photonic crystal fibers based on microfluidics includes the following steps: Weigh 200g of an aqueous dispersion of carboxylated polymethyl methacrylate monodisperse colloidal particles with a particle size of 350nm, a polydispersity index of 0.050, and a solid content of 5wt%.
[0054] Add 1.2 g of carbonyl imidazole to an aqueous dispersion of monodisperse colloidal particles. Activate the solution by stirring at 500 rpm for 5 hours in a constant temperature water bath at 80°C to obtain the activated solution.
[0055] Add 16g of acrylic acid dropwise to the activated dispersion. Maintain an 80°C water bath and a 500rpm stirring speed, and continue stirring for 8 hours to allow the acrylic acid to be grafted onto the surface of the polymethyl methacrylate colloidal particles, thus obtaining the modified solution.
[0056] The reacted colloidal particle dispersion was centrifuged at 10,000 rpm for 10 minutes, and the supernatant was discarded. The precipitate was redispersed in deionized water and sonicated for 10 minutes to prepare a dispersion with a mass concentration of 50 wt%. Then, 1.5 wt% of the photoinitiator 2-hydroxy-2-methylphenylacetone and 5 wt% of the crosslinking agent N,N'-methylenebisacrylamide were added, and the mixture was sonicated for another 10 minutes in the dark to form the precursor solution.
[0057] The aforementioned precursor solution was loaded into a syringe, which was then attached to a microinjection pump and injected into a hydrophobically treated polymethyl methacrylate microfluidic chip with a square cross-section and a width of 1000 μm. The injection flow rate was controlled at 100 μL / min to induce the orderly self-assembly of colloidal particles, forming wet gel fibers from within the microchannel.
[0058] A 370nm ultraviolet LED light source was placed above the chip, and the irradiation intensity was set to 200mW / cm² to irradiate the wet fibers in a flowing state in situ for 20 minutes.
[0059] The prepared photonic crystal fibers were collected in a petri dish and dried in a 60°C forced-air drying oven to obtain self-supporting photonic crystal fibers with a red structural color. The tensile strength of the obtained fibers was 10 MPa and the elongation at break was 200%.
[0060] Example 4 A method for fabricating self-supporting photonic crystal fibers based on microfluidics, which includes the following steps based on Example 1: Weigh 200g of an aqueous dispersion of carboxylated tert-butyl polyacrylate monodisperse colloidal particles with a particle size of 260nm, a polydispersity index of 0.027, and a solid content of 12wt%.
[0061] Add 0.8 g of carbonyl imidazole to an aqueous dispersion of monodisperse colloidal particles. Activate the solution by stirring at 400 rpm for 3 hours in a constant temperature water bath at 60°C to obtain the activated solution.
[0062] Add 12g of acrylamide dropwise to the activated dispersion. Maintain a 60°C water bath and a 400rpm stirring speed, and continue stirring for 6 hours to allow the acrylamide to be grafted onto the surface of the polytert-butyl acrylate colloidal particles, thus obtaining the modified solution.
[0063] The reacted colloidal particle dispersion was centrifuged at 12,000 rpm for 5 minutes, and the supernatant was discarded. The precipitate was redispersed in deionized water and sonicated for 20 minutes to prepare a dispersion with a mass concentration of 40 wt%. Subsequently, 2-hydroxy-2-methylphenylacetone (1.3 wt% of the total mass of the dispersion) and N,N'-methylenebisacrylamide (2 wt% of the total mass of the dispersion) were added as photoinitiators, and the mixture was sonicated for another 5 minutes in the dark to form a precursor solution.
[0064] The aforementioned precursor solution was loaded into a syringe, which was then installed in a microinjection pump and injected into a hydrophobic polymethyl methacrylate microfluidic chip with a rectangular channel cross-section, a length of 300 μm, and a width of 500 μm. The injection flow rate was controlled at 80 μL / min to induce the orderly self-assembly of colloidal particles, forming wet gel fibers from within the microchannel.
[0065] A 370nm ultraviolet LED light source was placed above the chip, and the irradiation intensity was set to 100mW / cm² to irradiate the wet fibers in a flowing state in situ for 10 minutes.
[0066] The prepared photonic crystal fibers were collected in a petri dish and dried in a 50°C forced-air drying oven to obtain self-supporting photonic crystal fibers with a green structural color. The tensile strength of the obtained fibers was 5.4 MPa and the elongation at break was 600%.
[0067] Comparative Example 1 Based on Example 1, if the monodisperse particles are not modified with polymerizable functional groups and are directly used for the preparation of self-supporting photonic crystal fibers based on microfluidics, the following steps are included: Weigh 200g of an aqueous dispersion of carboxylated polystyrene monodisperse colloidal particles with a particle size of 220nm and a polydispersity index of 0.020. The mass concentration of the aqueous dispersion of monodisperse colloidal particles is 10wt%. Centrifuge the colloidal particle dispersion at 12000rpm for 15 minutes, discard the supernatant, redisperse the precipitate in deionized water, and sonicate for 10 minutes to prepare a dispersion with a mass concentration of 40wt%. Continue sonicating in the dark for another 10 minutes to form the precursor solution.
[0068] The aforementioned precursor solution was loaded into a syringe, which was then attached to a microinjection pump and injected into a hydrophobically treated polymethyl methacrylate (PMMA) microfluidic chip with a circular cross-section and an inner diameter of 800 μm. The injection flow rate was controlled at 50 μL / min to induce the orderly self-assembly of colloidal particles, forming wet gel fibers from within the microchannel.
[0069] The prepared wet photonic crystal fibers were collected in a petri dish and dried in a 40°C forced-air drying oven to obtain self-supporting photonic crystal fibers with a blue structural color.
[0070] Mechanical property tests were conducted on the fibers obtained in this comparative embodiment. The fibers were found to be extremely brittle and have very low mechanical strength. They would break or pulverize under slight external forces (such as being touched by tweezers or experiencing airflow disturbances), failing to meet the basic requirements for flexibility in subsequent processing and practical applications. This indicates that although uncrosslinked and uncured photonic crystal fibers possess photonic bandgap characteristics, they cannot form a stable mechanical support network because the particles are only bound together by physical forces.
[0071] Comparative Example 2 Photonic crystal fibers were prepared using carboxylated polystyrene colloidal particles with a polydispersity index of 0.170 as building blocks, following the method described in Example 1.
[0072] Optical characterization of the fibers obtained in this comparative embodiment revealed that due to the excessively wide particle size distribution of the building blocks, the particles were unable to form a long-range ordered periodic structure during self-assembly, resulting in the disappearance of the photonic bandgap. The resulting fibers were entirely white, with no structural color visible, demonstrating that when the PDI is above the threshold of 0.05, even with the introduction of chemical cross-linking, it is still impossible to obtain colored fibers with photonic crystal properties.
[0073] Test method: This invention tests the mechanical properties of the crystalline fibers prepared in the examples and comparative examples using a universal testing machine. The fiber samples were cut into standard specimens with a length of 50 mm, with a clamping distance of 20 mm and a tensile speed of 10 mm / min. To ensure the accuracy and statistical significance of the data, each sample was tested at least three times in parallel, and the average value was taken as the final test result. The testing environment was controlled under standard temperature and humidity conditions (temperature 25 ± 2℃, relative humidity 40% ± 5%). The test results are shown in Table 1.
[0074] Table 1. Mechanical property test data for the examples and comparative examples. Example 1 5.7 510 Example 2 5.0 800 Example 3 10.0 200 Example 4 5.4 600 Comparative Example 1 / / Comparative Example 2 5.6 500 As shown in Table 1, the self-supporting photonic crystal fiber prepared by this invention achieves a breakthrough improvement in mechanical properties, effectively solving the technical problems of high brittleness and difficulty in bending of traditional photonic crystal materials. Specifically, the fibers of Examples 1 to 4 all exhibit excellent comprehensive mechanical properties, with elongation at break reaching 200% to 800%, fully demonstrating that the fiber possesses extremely high flexibility and ductility, capable of withstanding large-scale stretching and bending without easily breaking, providing reliable mechanical protection for subsequent flexible weaving processing. Meanwhile, the tensile strength of each example remains between 5.0 MPa and 10.0 MPa, indicating that the fiber possesses sufficient mechanical strength while being highly flexible, ensuring that the internal structure does not collapse during the weaving process and daily use, maintaining the stability and durability of the structural color. Furthermore, Comparative Example 1 could not form continuous fibers, and the comprehensive performance of Comparative Example 2 was inferior to the preferred solution of this invention. These positive and negative examples confirm that the preparation method of this invention plays an irreplaceable key role in obtaining photonic crystal fibers that combine "self-support" and "superelasticity," highlighting the creativity and application value of the technical solution of this invention.
[0075] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described in this invention to avoid redundancy. Although preferred embodiments of this invention have been described, those skilled in the art, once they understand the inventive concept of this invention, can make other changes and modifications to these embodiments, and all such changes and modifications fall within the scope of this invention.
[0076] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. If such modifications and variations fall within the scope of equivalents of this invention, then this invention also intends to include these modifications and variations.
Claims
1. A method for fabricating a self-supporting photonic crystal fiber based on microfluidics, characterized in that, Includes the following steps: Preparing precursor solutions of monodisperse colloidal particles modified with polymerizable functional groups; The precursor solution is injected into the channel of the microfluidic chip to form wet gel fibers in a flowing state. In-situ ultraviolet irradiation treatment was performed on wet gel fibers in a flowing state to obtain gel fibers with cross-linked networks; Desolventize the gel fiber with cross-linked network to obtain self-supporting photonic crystal fiber; The preparation method of the polymerizable functional group modified monodisperse colloidal particle precursor liquid includes: An activated solution is obtained by activating a monodisperse colloidal particle aqueous dispersion with a functional group activator. The activated liquid was modified with functional monomers to obtain a modified liquid; The modified solution was centrifuged, the precipitate was redispersed in water, and a photoinitiator and a crosslinking agent were added to obtain a precursor solution of monodisperse colloidal particles modified with polymerizable functional groups.
2. The preparation method according to claim 1, characterized in that, The monodisperse colloidal particles include at least one of carboxylated silica colloidal particles, carboxylated polystyrene colloidal particles, carboxylated polymethyl methacrylate, and carboxylated tert-butyl acrylate.
3. The preparation method according to claim 1, characterized in that, The monodisperse colloidal particles have a particle size of 180nm~350nm and a polydispersity index of not higher than 0.050 and not 0.
4. The preparation method according to claim 1, characterized in that, The group activator is at least one selected from 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, and carbonyldiimidazole; And / or, the functional monomer is at least one of hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylic acid, and acrylamide.
5. The preparation method according to claim 1, characterized in that, In the process of preparing the precursor solution of the polymerizable functional group-modified monodisperse colloidal particles, the mass concentration of the aqueous dispersion of the monodisperse colloidal particles is 5%~15%; And / or, in the process of preparing the precursor solution of the polymerizable functional group-modified monodisperse colloidal particles, the functional group activator accounts for 0.2% to 0.6% of the total mass of the monodisperse colloidal particle aqueous dispersion; And / or, in the process of preparing the precursor liquid of the polymerizable functional group-modified monodisperse colloidal particles, the functional monomer accounts for 2% to 8% of the total mass of the aqueous dispersion of the monodisperse colloidal particles.
6. The preparation method according to claim 1, characterized in that, The photoinitiator includes 1-[4-(2-hydroxyethoxy)phenyl]-2-hydroxy-2-methyl-1-propanone or 2-hydroxy-2-methylphenylpropanone; And / or, the crosslinking agent includes at least one of N,N'-methylenebisacrylamide, ethylene glycol dimethacrylate, and trimethylolpropane triacrylate.
7. The preparation method according to claim 1, characterized in that, Based on the total mass of the monodisperse colloidal particle precursor liquid modified with polymerizable functional groups, the mass concentration of the monodisperse colloidal particles is 30%~50%; the mass concentration of the photoinitiator is 0.5%~1.5%; and the mass concentration of the crosslinking agent is 0.5%~5%.
8. The preparation method according to claim 1, characterized in that, The activation temperature during the activation treatment is 40℃~80℃, and the activation time is 2h~5h; And / or, the reaction temperature during the modification treatment is 40℃~80℃, and the reaction time is 4h~8h; And / or, the wavelength of in-situ ultraviolet irradiation is 250nm~370nm, the irradiation intensity is 10mW / cm²~200mW / cm², and the irradiation time is 5min~20min; And / or, the agent is volatilized by natural air drying or heating and drying, with a volatilization temperature of 20℃~60℃.
9. A self-supporting photonic crystal fiber based on microfluidics, characterized in that, The hollow photonic crystal fiber prepared by any one of claims 1 to 9 has a tensile strength of 5 MPa to 10 MPa and an elongation at break of 200% to 800%.
10. The application of the microfluidic-based self-supporting photonic crystal fiber of claim 9 in the fabrication of flexible wearable light-emitting devices or smart color-changing textiles.